CREATION OF A SMART LIGHTING SYSTEM IN THE STUDY ROOM - Turashova, Sh.; Amangeldin, A.; Seiduali, K.; Tekesbayeva, N.; Yersin, M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The relevance of the introduction of innovative technologies in the educational process is steadily growing. Today, smart lighting is increasingly found in homes and offices, but it is still rare in schools and universities. The lack of ready-made solutions for classrooms is explained by the specific requirements for flexibility and efficiency of lighting, as well as the expediency of creating various lighting scenarios in an educational environment. "Smart lighting" in the classroom should include automatic brightness control depending on the time of day and natural lighting, changing the color temperature of the light to create an optimal, comfortable atmosphere depending on the time of day, uniform lighting settings for each workplace, integration with other smart classroom systems. The purpose of this study is to study the influence of various lighting parameters (brightness, color temperature, dynamics) on cognitive functions, emotional state, on the level of concentration and academic performance of students; with this in mind, the creation of a prototype smart lighting system for the classroom, which will optimize energy consumption and create comfortable learning conditions.